Adição de óleo de Citrus sinensis na dieta de tilápia-do-Nilo: desempenho produtivo, perfil hematológico e atividade respiratória de leucócitos - Lima, Bruno Tadeu Marotta [UNESP] (2015)
Orange essential oil (OEC) - Citrus sinensis, is a herbal medicine extracted byproduct of the citrus industry residue, recognized as a safe alternative in foods such as antimicrobial agent and in the treatment of diseases. The present study was conducted to determine the effects of orange essential oil in the diet of tilapia (Oreochromis niloticus) on growth performance, haematological and immunological parameters in resistance against Streptococcus agalactiae. The fish were submitted to five treatments (0, 50, 100, 200 and 400 mg kg-1), which was the inclusion levels in orange essential oil feed levels in the control group (positive control, negative control) and the group treated the orange essential oil, incorporated in the diets. We investigated the respiratory activity of leukocytes, hematological (hematocrit, hemoglobin, red blood cell count, white blood cell differential count) and evaluation of animal performance (condition factor, weight gain percentage, feed conversion, specific growth rate, weight gain and survival). The results of this study showed that the use of OEC showed no significant effect on the performance of tilapia, when compared with the control. However, the OEC promoted a significant improvement in blood parameters and respiratory activity of leukocytes of tilapia challenged with S. agalactiae, when compared to the control, indicating that this herbal medicine can be used as an antimicrobial agent as an alternative to antibiotics